Clinical trials for coronavirus disease 2019: What is being evaluated and what is not - Arabi, Yaseen M. (Ann Thorac Med, 2020)
Since the report of the first case of coronavirus disease 2019 (COVID-19) in China in late December 2019, there have been 204 610 cases worldwide as of 18 March, 2020. As part of the response to this outbreak, there has been an impressive amount of research undertaken to better characterize the disease and to evaluate therapeutic options. By March 12, 2020, there are more than 382 studies registered in the clinical trials databases addressing COVID-19 including more than 80 randomized controlled trials.